MXene based emerging materials for supercapacitor applications: Recent advances, challenges, and future perspectives - Panda, Subhasree; Deshmukh, Kalim; Khadheer Pasha, S.K.; Theerthagiri, Jayaraman; Manickam, Sivakumar; Choi, Myong Yong (Coordination chemistry reviews, 2022)
•Recent progress in MXene based supercapacitive energy storage is reviewed.•Top-down and bottom-up MXene synthesis methods are discussed.•Unique properties of MXenes have been reviewed.•Charge storage mechanism of various MXene based supercapacitors are dsicused. In the past few decades, with the advancement of technology, there has been an increasing demand for high-capacity energy storage devices having durability, low production cost, and flexibility. MXene, a layered 2D transition metal carbide, nitride or carbonitride, exfoliated from its parent MAX phase by selective chemical etching of covalently bonded A layer has become the most emerging material today for energy storage applications. The 2D layered structure, atomic layer thickness, high conductivity, tunable surface functional groups, superior hydrophilicity, good mechanical properties, excellent electrochemical nature, flexibility, and the ease of preparation of MXene has made it the most demanding material today among 2D families. Starting from gas and biosensors, water purification, water splitting, photo and electrocatalysis, transparent conductors in electronics, antibacterial film, electromagnetic interference shielding, and in batteries and supercapacitors, MXene have a wide range of applications. The special properties of MXene have made scientists work on its further theoretical and experimental developments. This article mainly reviews the recent advances of MXene for fabricating durable, pliable, and highly efficient electrochemical energy storage devices using supercapacitors as its power source. The structure of MXene, different synthesis methods, and their unique properties have been deeply studied, as well as the effect of various factors like size and shape of MXene sheets, design of electrode architecture, nature of electrolyte, etc. on the electrochemical performance and charge storage mechanism of MXene based supercapacitors have been emphasized. This article also throws light on state-of-the-art recent progress in MXene composite-based supercapacitors. Finally, its challenges and future advances have been discussed.